Contribuição do modelo do Ligante Biótico (BLM) para o estabelecimento de critério de qualidade de água superficial para cobre na região de Carajás, PA - Flavio Dairo Cafe de Castro (2009)
The main objectives of this study were evaluate the effectiveness of the BLM (Biotic Ligand Model) in predicting acute and chronic copper toxicity for waterbodies in the Carajás region (Pará, Brasil) and contribute to the establishment of water quality criteria for the protection of aquatic communities. BLM is a model that considers the aquaticphysicochemical properties as relevant parameters for mitigating the toxic effects of metals to aquatic biota. Considering the metal speciation and interactions with other constituents of the aqueous phase, the model simulates the bioavailability and toxic effects on aquaticorganisms. Three field surveys were carried out, seasonally. For each field survey water samples were collected at three different points in two areas - Sossego Mine and Salobo Project. Water samples were submitted to physicochemical analysis and toxicological assays (acute and chronic). Measured laboratory toxicological results were compared with predicted results (BLM). For acute toxicity the model demonstrated to be robust because it was able to predict the toxicity of copper with high degree of accuracy for the two areas in both field surveys. Correlation between physicochemical parameters and toxicity showed that BLMs theoretical and experimental principles were corroborated by these studies considering that the mitigating factors of toxicity really contributed to the EC50 increase. For chronic toxicity BLM was able to model a significant number of points (2/3 of total) but didnt have enough sensitivity to separate the toxicity per area and seasons, indicating aneed for further development and understanding of the mechanisms linking physical and chemical characteristics, physiology and toxicity. Chronic toxicity results may have been affected by natural toxicity observed in the laboratory, but it was unclear to what extent thisfact influenced the final results. From a regulatory point of view the results of three parameters for protection of aquatic communities were compared with the maximum allowed value in the Brazilian legislation (CONAMA Resolution 357/2005). Despite the small number of samples collected in each area and also the limited number of fieldsurveys, it can be said that the maximum allowed value for copper in Class 2 waterbodies are consistent for the protection of aquatic communities in the area of Salobo Project but relatively conservative in the area of Sossego Mine, indicating the need of obtaining local water quality criteria, based on robust and reliable environmental andtoxicological data.